Molecular identification of purebredness and kinship of the Philippine crocodile (Crocodylus mindorensis) and the Cuban crocodile (C. rhombifer) for ex situ conservation management - Straková, Helena (Jihočeská univerzita, 2014)
The current status of crocodilians recognizes them as a group under serious threat due to their habitat destruction and illegal poaching for their lucrative products. In addition to these threats, the elimination of spatial and temporal boundaries through modern anthropogenic pressures has facilitated hybridization in crocodiles by bringing together species that would otherwise not breed due to lack of opportunity. Here analyzed crocodiles, the Philippine crocodile (Crocodylus mindorensis) and the Cuban crocodile (Crocodylus rhombifer) are critically endangered and listed in CITES Appendix I. This study deals with a significant portion of the Philippine and Cuban crocodile captive population in Europe based on mtDNA, nucDNA and microsatellites. The species genetical purity of 13 specimen of C. mindorensis was determined on the ground of testing maternally inherited mitochondrial gene cytochrome b and and D-loop loci from the mitochondrial control region as well as two nuclear markers, LDHA and C-mos. Also the purity of 11 out of mentioned 13 individuals on the basis of several (7) microsatellite loci, while possibly confirming a supposed hybrid origin of two crocodiles with mixed morphotype. Then a purity of 4 samples of the Cuban crocodile was verified with cyt b gene and nuclear DNA purity of all 7 tested individuals with LDHA gene and 13 microsatellites. Based on the obtained genetic characters I proceeded a likely kinship of the two groups of crocodiles and subsequently suggested an optimal breeding management within the ex-situ conservation
Molecular identification of purebredness and kinship of the Philippine crocodile (Crocodylus mindorensis) and the Cuban crocodile (C. rhombifer) for ex situ conservation management